Intrathecal cannabinoid administration suppresses noxious stimulus-evoked Fos protein-like immunoreactivity in rat spinal cord: comparison with morphine. - Hohmann Andrea G; Tsou Kang; Walker J Michael (Acta Pharmacologica Sinica; Vol 20, No 12 (December 1999): Acta Pharmacologica Sinica, 2016)
AIM: To determine whether cannabinoids suppress noxious stimulus-evoked Fos protein-like immunoreactivity (FLI) through direct actions at the spinal level. METHODS: Rats were implanted with intrathecal (ith) catheters at least one week prior to evaluation in the formalin test. Effects of the cannabinoid agonist, CP55,940 (80 micrograms ith) on formalin pain and FLI in rat spinal cord were compared with that of the prototypic narcotic analgesic, morphine (20 micrograms ith). CP55,940 suppressed pain behavior and FLI induced by intraplantar formalin. The cannabinoid suppressed Fos in the neck region of the dorsal horn and in the ventral horn, but not in the nucleus proprius. The efficacy of the cannabinoid in suppressing FLI in these laminae and pain behavior was comparable to morphine administered via the same route. However, only morphine suppressed FLI in the superficial dorsal horn relative to vehicle treatment. CONCLUSION: Cannabinoids suppress nociceptive processing, in part, through actions at the spinal level. However, morphine showed greater potency and efficacy than CP55,940 in suppressing formalin-induced FLI following spinal administration.